The Crisis of Predatory Publishing in the Post-Soviet Space - Qoraboyev, Ikboljon (International Higher Education, 2023)
Integration into the global knowledge economy through internationalization was believed to be a major factor for transformation of higher education systems in the post-Soviet space. Transition and transformation were major paradigms through which we analyzed higher education developments. Instead, we witness the emergence of two parallel research cultures. The issue of predatory publishing helps us to see this phenomenon more clearly. Predatory publishing is transforming into a self-perpetuating culture.